2007
DOI: 10.1590/s1807-59322007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Central Venous Catheter-Related Infections in Pediatric Intensive Care

Abstract: Vilela R, Jácomo ADN, Tresoldi AT. Risk factors for central venous catheter-related infections in pediatric intensive care. Clinics. 2007;62(5):537-44. OBJECTIVES:To identify risk factors for short-term percutaneously inserted central venous catheter-related infections in children and to evaluate the accuracy of a mortality score in predicting the risk of infection. METHOD: After reviewing the charts of patients who developed catheter-related infection in a university hospital's pediatric intensive care unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
1
18
0
5
Order By: Relevance
“…Our analysis confirmed a CVC duration ≥7 days as a risk factor for the development of a catheter-related infection and a prolonged duration of total parenteral nutrition as a risk factor for central line-associated bloodstream infections [8,9]. In particular, this survey showed that the risk of central line-associated bloodstream infections is already increased after 5 days of total parenteral nutrition administration.…”
Section: Discussionsupporting
confidence: 70%
“…Our analysis confirmed a CVC duration ≥7 days as a risk factor for the development of a catheter-related infection and a prolonged duration of total parenteral nutrition as a risk factor for central line-associated bloodstream infections [8,9]. In particular, this survey showed that the risk of central line-associated bloodstream infections is already increased after 5 days of total parenteral nutrition administration.…”
Section: Discussionsupporting
confidence: 70%
“…A avaliação de variáveis relacionadas à inserção e manutenção de CVC dos pacientes de uma UTI pediátrica (UTIP) identificou, através de análise de regressão logística, os seguintes fatores de risco para as infecções relacionadas ao CVC: insuficiência respiratória; duração da internação; tempo de intubação; inserção do cateter na UTI e uso de NP; inserção de mais de um cateter (p = 0,014); e tempo de permanência do cateter (p = 0,0013) 17 .…”
Section: Fatores De Riscounclassified
“…Dentre os fatores de risco para sepse na população pediátrica atendida em UTI que são diferentes daqueles encontrados em serviços direcionados para atendimento de pacientes adultos, encontra-se o local de inserção do cateter, pois não há evidência de maior risco para infecção quanto ao sítio de implante em subclávia, jugular ou femoral, como é demonstrado em pacientes adultos 12,17 . Sabe-se que crianças apresentam fragilidade da rede venosa, e a utilização do cateter central para coleta de material para exames é comum; por isso, o CVC pode ser mantido por tempo maior do que o necessário, para garantir um acesso venoso seguro.…”
Section: Fatores De Riscounclassified
“…The incidence of Staphylococcus aureus as the etiologic agent of bloodstream infections was greater than the incidence of coagulase-negative Staphylococcus, which has been observed before in pediatric and neonatal intensive care units in South America (9,22) . Enterococcus sp was not identified as an agent of infection among this sample, despite its ascendancy in the United States.…”
Section: Discussionmentioning
confidence: 74%